Wild Origins of Macadamia Domestication Identified Through Intraspecific Chloroplast Genome Sequencing - Nock, Catherine J.; Hardner, Craig M.; Montenegro, Juan D.; Ahmad Termizi, Ainnatul A.; Hayashi, Satomi; Playford, Julia; Edwards, David; Batley, Jacqueline (Frontiers in Plant Science, 2019)
Identifying the geographic origins of crops is important for the conservation and utilisation of novel genetic variation. Even so, the origins of many food crops remain elusive. The tree nut crop macadamia has a remarkable domestication history, from subtropical rain forests in Australia through Hawaii to global cultivation all within the last century. The industry is based primarily on Macadamia integrifolia and M. integrifolia-M. tetraphylla hybrid cultivars with Hawaiian cultivars the main contributors to world production. Sequence data from the chloroplast genome assembled using a genome skimming strategy was used to determine population structure among remnant populations of the main progenitor species, Macadamia integrifolia. Phylogenetic analysis of a 506 bp chloroplast SNP alignment from 64 wild and cultivated accessions identified phylogeographic structure and deep divergences between clades providing evidence for historical barriers to seed dispersal. High levels of variation were detected among wild accessions. Most Hawaiian cultivars, however, shared a single chlorotype that was also present at two wild sites at Mooloo and Mt Bauple from the northernmost distribution of the species in south-east Queensland. Our results provide evidence for a maternal genetic bottleneck during early macadamia domestication, and pinpoint the likely source of seed used to develop the Hawaiian cultivars. The extensive variability and structuring of M. integrifolia chloroplast genomic variation detected in this study suggests much unexploited genetic diversity is available for improvement of this recently domesticated crop.